Contribution of Children's Literature in the Formation of Character of Elementary School Children - Ni Putu, Eni Astuti; Ni Made Rely Indah Sari (Mudra Jurnal Seni Budaya, 2024)
This study aims to describe the contribution of children's literature in character education and the selection of children's literature according to the developmental stage of elementary school children. This study is a qualitative-descriptive study of the library research type. Data collection techniques are by searching for sources and constructing from books on children's literature and accredited journals, then analyzing critically and in-depth. Based on the results of data analysis, it can be explained that the contribution of children's literature to the emotional aspect is obtained from demonstrations of life as demonstrated by the characters in the story so that children will learn how to manage their emotions so as not to harm themselves and others. In the intellectual aspect, children's literature contains sequencing and plot logic to support children's use of their minds to think, understand and criticize the stories they get. In the aspect of imagination, literature in its stories can attract the child's entire self. With this, the child gains an extraordinary experience that is significantly correlated with creativity and will provoke the growth and development of creativity. In the social aspect, children's literature demonstrates character interactions so that it supports children in maximizing their development in their proximal development zone. In addition, from an educational aspect, children's literature is connected to aspects of exploration and discovery, language, beauty, multicultural insight, and children's reading habits that influence reading habits and literacy culture, which are very necessary in facing the progress of science and technology in this era.